2020
DOI: 10.1002/jobm.202000059
|View full text |Cite
|
Sign up to set email alerts
|

The ctnFgene is involved in citrinin and pigment synthesis inMonascus aurantiacus

Abstract: The application of Monascus is restricted by citrinin. So, it is important to explore the synthetic pathway of citrinin to completely inhibit the production of citrinin. In our previous study, we found that the protein encoded by the ctnF gene has a significant similarity to fructose‐2,6‐bisphosphatase (F26BPase). It is generally known that the bifunctional enzyme F26BPase regulates the glycolytic flux. So, we speculated that the CtnF protein strengthens carbon flux towards acetyl‐CoA and malonyl‐CoA which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…These changes may be responsible for the lower yield of acetyl-coA (Figure 3D). Li et al [36] found that ctnF, an enzyme involved in CIT synthesis, exerted regulatory control over glycolytic flux, subsequently impacting CIT yield. Disruption of the pksCTα gene was found to hinder the transformation of glycerate-2P to phosphoenol-pyruvate, resulting in reduced enolase activity compared with M7.…”
Section: Discussionmentioning
confidence: 99%
“…These changes may be responsible for the lower yield of acetyl-coA (Figure 3D). Li et al [36] found that ctnF, an enzyme involved in CIT synthesis, exerted regulatory control over glycolytic flux, subsequently impacting CIT yield. Disruption of the pksCTα gene was found to hinder the transformation of glycerate-2P to phosphoenol-pyruvate, resulting in reduced enolase activity compared with M7.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the amplification and expression of these two key genes serve as complementary methods for screening CIT-free/low-CIT Monascus strains . These findings have contributed to the mining and validation of several genes directly involved in CIT biosynthesis, including ctnB , ctnE , ctnF , and orf7 . Acetyl coenzyme A and malonyl coenzyme A are the initial substrates for the synthesis of both pigments and CIT, and the metabolic flow of these substrates is disrupted when one of their synthetic pathways is blocked. Therefore, selecting the appropriate Monascus strains, including engineered strains with reduced or absent CIT production, can significantly mitigate CIT contamination during manufacturing, thereby enhancing the fermentation quality of cheese products.…”
Section: Control Of Cit Contamination In Cheese Productsmentioning
confidence: 99%